FAKTOR-FAKTOR YANG MEMPENGARUHI MARGIN MURABAHAH BANK SYARIAH DI INDONESIA - Yusro Rahma (Akuntabilitas, 2016)
The purpose of this study to examine the factors that influence the margin murabaha them, profit targets are proxied by return on assets (ROA), overhead costs, the results of third-party funds and financing. This study used 11 samples of Islamic banking in Indonesia, with criteria has published annual reports and the necessary data available. This study uses regression analysis to examine the factors that influence the margin murabaha. The results of this study showed that the return on assets, overheads and no effect on the financing murabaha margin partially, but the results showed that the results of DPK affect the margin murabaha.DOI: 10.15408/akt.v9i1.3584